Equivalent circuit models using CPE for impedance spectroscopy of electronic ceramics - Pandey S.; Kumar D.; Parkash O.; Pandey L. (My University, 2025)
Complex immittance (Impedance Z, Modulus M, Admittance Y, Permittivity ϵ) spectra for some equivalent circuit models involving resistances, capacitances and constant phase angle elements (CPE) are calculated for different ratios of the parameters. A comparison of experimentally obtained complex immittance plots with these diagrams greatly facilitates the search for the most appropriate equivalent circuit representing the electrical properties of electronic ceramics. An equivalent circuit for Ba1-xSrxTiO3 (x = 0.35) ceramic system is developed by using these simulated plots. © 2017 Taylor & Francis Group, LLC.